2023
DOI: 10.21873/invivo.13126
|View full text |Cite
|
Sign up to set email alerts
|

Diosgenin, a Natural Steroidal Sapogenin, Alleviates the Progression of Diabetic Retinopathy in Diabetic Mice

Abstract: Background/Aim: Diabetic retinopathy (DR) is the most common microvascular complication of diabetes and a major cause of blindness in working-age adults. Diosgenin (DG), a natural steroidal sapogenin extracted from fenugreek seeds and wild yam roots, has hypolipidemic, hypoglycemic, anticancer, and anti-inflammatory properties. Given its pharmacological effects, we speculated that DG may be a promising treatment for DR. Therefore, this study was aimed at evaluating the effectiveness of DG in preventing or slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Therefore, it can be reasonably believed that diosgenin is the core ingredient of JGSQ. Many studies have also proven that diosgenin can improve many complications of diabetes, such as diabetic nephropathy [ 39 ], nonalcoholic fatty liver disease in type 2 diabetes [ 40 ], cognitive impairment [ 41 ], as well as DR [ 42 , 43 ] Therefore, this study used AKT, GAPDH, TNF, TP53, and IL-6 as the core targets of JGSQ's action, and the above five targets are the main molecules that regulate cell proliferation and inflammation. Subsequently, this study further validated the expression of cleaved PARP and TP53 through western blotting and found that JGSQ can downregulate the expression of cleaved PARP and TP53.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be reasonably believed that diosgenin is the core ingredient of JGSQ. Many studies have also proven that diosgenin can improve many complications of diabetes, such as diabetic nephropathy [ 39 ], nonalcoholic fatty liver disease in type 2 diabetes [ 40 ], cognitive impairment [ 41 ], as well as DR [ 42 , 43 ] Therefore, this study used AKT, GAPDH, TNF, TP53, and IL-6 as the core targets of JGSQ's action, and the above five targets are the main molecules that regulate cell proliferation and inflammation. Subsequently, this study further validated the expression of cleaved PARP and TP53 through western blotting and found that JGSQ can downregulate the expression of cleaved PARP and TP53.…”
Section: Discussionmentioning
confidence: 99%
“…For example, diosgenin (DG), a natural steroidal sapogenin, increased Bcl-2 expression while decreasing cleaved caspase-3, thus playing a central role in inhibiting RGCs apoptosis (Liao et al. 2023 ). Jin-Gui-Shen-Qi Wan (JGSQ), first recorded in ‘Essentials from the Golden Cabinet’ and used for thousands of years in China since the Eastern Han dynasty (Hu et al.…”
Section: Methodsmentioning
confidence: 99%
“…Liao et al demonstrated that diosgenin increased the total retinal thickness, photoreceptor layer, and outer nuclear layer thickness, and ameliorated ganglion cell loss in the db/db mouse model. Additionally, diosgenin was shown to increase Bcl-2 expression while reducing caspase-3 expression, suggesting its potential as an anti-apoptosis agent in vivo [ 114 ]. These studies suggest that fenugreek and its extracts may serve as a new modality for DR treatment.…”
Section: Natural Products In the Treatment Of Diabetic Retinopathymentioning
confidence: 99%
“…Reduced the inflammatory response and oxidative stress of ARPE-19 cells 4. Activated the AMPK/Nrf2/HO-1 pathwayAMPK/Nrf2/ HO-1[113,114]…”
mentioning
confidence: 99%